Asset Pricing and the Carbon Beta of Externalities - Ottmar Edenhofer; Kai Lessmann; Ibrahim Tahri (Center for Economic Studies and ifo Institute (CESifo), 2021)
Climate policy needs to set incentives for actors who face imperfect, distorted markets and large uncertainties about the costs and benefits of abatement. Investors price uncertain assets according to their expected return and risk (carbon beta). We study carbon pricing and financial incentives in a consumption-based asset pricing model distorted by technology spillover and timeinconsistency. We find that both distortions reduce the equilibrium asset return and delay investment in abatement. However, their effect on the carbon beta and risk premium of abatement can be decreasing (when innovation spillovers are not anticipated) or increasing (when climate policy is not credible). Efficiency can be restored by carbon pricing and financial incentives, implemented in our model by a regulator and by a long-term investment fund. The regulator commands carbon pricing and the fund provides subsidies to reduce technology costs or to boost investment returns. The investment subsidy creates a financial incentive that complements the carbon price. In this way the investment fund can support climate policy when the actions of the regulator fall short. These instruments must also consider the investment risk and the sequence of their implementation. The investment fund can then pave the way for carbon pricing in later periods by preventing a capital misallocation that would be too expensive to correct. Thus the investment fund improves the feasibility of ambitious carbon pricing.
Keywords: Q54; D81; G12; 330; carbon budget; CCAPM; policy instruments; external effect